Rapid visual detection and differentiation of canine and feline parvovirus via a one-tube RPA-CRISPR/Cas13a assay - Shao, Zhurui; Zhang, Wenkai; Jin, Changbin; Yang, Zhibo; Yang, Jingyi; Zhang, Xiaohu; Huang, Xintong; Yang, Yufei; Ren, Ruizi; Zhang, Yiwen; Weng, Jieen; Zhang, Yueping; et al. (Frontiers in Microbiology, 2025)
Canine parvovirus type 2 (CPV-2) and feline parvovirus (FPV) are highly contagious pathogens that pose significant threats to domestic and wild carnivores. Rapid and accurate diagnosis is crucial for outbreak control and wildlife conservation, especially in resource-limited settings. In this study, we developed a one-tube RPA-CRISPR/Cas13a platform for the rapid detection and differentiation of CPV-2 and FPV. Two systems were established: a universal detection system for simultaneous identification of both viruses, and a differential detection system to distinguish between them. By targeting conserved regions of the VP2 gene and optimizing reaction conditions, we achieved high sensitivity and specificity. The universal system exhibited a limit of detection (LOD) of 102 copies/μL, while the differential system reached 103 copies/μL, with both assays completed within 60 min. Clinical validation using 50 samples showed 100% concordance with q-PCR and sequencing results. This study established a dual detection system that is sensitive, rapid, and suitable for use in primary-level settings and field conditions. It holds significant application value in enhancing the early diagnosis and differentiation of canine and feline parvoviruses, reducing the risk of transmission, and protecting the health of wildlife.